Psychological Characteristics and Entrepreneurial Intention: A Theory of Planned Behavior Approach - Mokhtar, Rozita; Zainuddin, Yuserrie (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2016)
The study is related to the intention to be entrepreneurs among Politeknik Sultan Haji Ahmad Shah (POLISAS) students and can be explained by Ajzen’s (1991) Theory of Planned Behavior. For this reason, this study firstly indicated the influence of psychological characteristics on entrepreneurial intention. Another part of this study is to point out the effect of psychological characteristics on attitudinal factors as well as the effect of attitudinal factors on entrepreneurial intention. The data were surveyed and gathered from final year diploma students from two fields of study (engineering and commerce) offered by POLISAS. A total of 100 questionnaires were distributed to the respondents but only 88 questionnaires were used in the statistical analyses. The results indicated that the hypothesized linkage between psychological characteristics and entrepreneurial intention was fully supported. The study also found that the hypothesized linkage between psychological characteristics and attitudinal factors were partially supported. Implications and limitations of the findings are specified for future study.